0908 Insomnia Symptoms Predict Suicide: Are Patients More Likely to Report Sleep Disturbance than Suicidal Ideation Before their Death?. (12th April 2019) - Simmons, Zach; Burlingame, Gary; Korbanka, Juergen; Eastman, Kevin; Thomas, Douglas; Christensen, Jeremy; Burton, Jed; Barron, David; Jenson, Michelle; Martin, Justin; Kay, Daniel
Abstract: Introduction: Insomnia is a risk factor for suicidal ideation, suicide attempts, and suicide. Due to stigma and fear of consequences, some patients who are seriously contemplating suicide may hesitate to report their suicidal ideations. Insomnia symptoms are far less stigmatizing and may serve as a potent marker for suicide even when patients do not report having suicidal ideations. The objective of this study was to determine whether self-reported symptoms of insomnia predict suicide, independent of self-reported suicidal ideation. Methods: The sample included deceased psychiatric patients seen at Weber Human Services since 2008 ( n =196) who completed the Outpatient Questionnaire-45.2 (OQ) prior to death. Frequency of suicidal ideation or insomnia prior to death were assessed using items from the OQ. Manner of death (suicide vs. other) was determined by death records; 19 died by suicide. History of suicidal ideation (yes vs. no) and suicide attempts (yes vs. no) were determined through the electronic medical records. With this information, cases were grouped into 4 categories: denied any history of suicidality, history of suicidal ideation only, suicide attempt history, or died by suicide. Insomnia frequency was compared across groups using Mann-Whitney U tests. Logistic regression was used to determine whether OQ reported insomnia frequency predicted suicide, adjusting for frequency of suicidal ideation reported on the OQ. Results: Compared to the non-suicidal group, the suicide attempt group and the suicide group reported significantly higher insomnia frequency, Z =3.3, p =0.001, Z =3.4, p =0.001. Greater insomnia frequency reported on the OQ, but not suicidal ideation, was a significant predictor of suicide, even after adjusting for suicidal ideation, W =3.9, p =0.049. Conclusion: Often overlooked, insomnia is a risk factor for suicidality. As the severity of suicidality increased from suicidal ideation to suicidal behavior, self-reported insomnia frequency increased. On the OQ administration completed closest to death, insomnia symptoms were a better predictor of suicide than suicidal ideation. Insomnia symptoms may be a valuable indicator of imminent suicide risk in psychiatric patients, even when suicidal ideation is denied. Support (If Any): n/a